Film continuity - Waddy, Colin; Halliday, Eric (North Ryde, NSW. : Australian Film Television & Radio School, 1981)
The program talks on continuity in film making
pt.1. What is continuity - pt.2. Screen direction - pt.3. The continuity girl
Keywords: Script clerks; Moving -- pictures -- Production and direction